The Study On Fungal Isolates From Ownership Dogs With Skin Lesions In Rural Areas Of Meshkin-Shahr With Emphasize On Transmission Risk Of Fungal Zoonoses - Solmaz Basiri; Roshanak Daie Ghazvini; Seyed Jamal Hashemi; Seyed Hossein Mirhendi; Mohsen Geramishoar; Zabihollah Zareie (Tehran University of Medical Sciences, 2015)
Background and Aim: Identification of possible animal sources of infection is applied for preventing the outbreak and progressive epidemics of infection. The aim of present study is isolation of pathogenic and opportunistic fungi from the skin of ownership dogs with emphasize on transmission risk of fungal zoonoses in rural areas of Meshkin Shahr, Ardebil province of Iran. Materials and Methods: This cross-sectional and descriptive study was performed in laboratory of Medical Mycology, School of Public Health, Tehran University of Medical Sciences from April 2011 to November 2012. Hundred and thirty dogs were studied. Collected scales and hair samples were examined by direct smear and SC, SCC and DTM culture with the aim of full coverage of whole fungal growth such as saprophytic and pathogenic fungi for 1-3 weeks. Results: From 130 examined samples, Alternaria 41 (31.5%) as the most frequent, Chaetomium 1 (0.9%) and Nattrassia 1 (0.9%) as the least frequent saprophytic agents, were isolated from the samples. Conclusion: The dogs in these areas are not the source of infection for dermatophytosis and had no role in the epidemiology of the disease